Dectin-1 and dectin-2 drive protection against Sporothrix brasiliensis in experimental sporotrichosis - Yoshikawa, Fabio Seiti Yamada; de Almeida, Sandro Rogerio; Saijo, Shinobu (Frontiers in Immunology, 2025)
IntroductionThe emerging fungal pathogen Sporothrix brasiliensis has been responsible for epidemic outbursts of sporotrichosis in Latin America, particularly Brazil, in recent years. The higher aggressiveness of the infection and its zoonotic nature are hallmarks of the pathogen, but the immunological markers of protection are not fully characterized. The C-type lectin receptors – dectin-1 and dectin-2 – drive key antifungal responses, and here we aimed to uncover their contribution against S. brasiliensis in a murine model of disseminated sporotrichosis.MethodsWild-type, Dectin-1 and/or Dectin-2 knockout, and IL-17A/F knockout C57BL/6J mice were challenged with S. brasiliensis in a model of systemic infection. Animals were monitored for parameters as survival and body weight loss. Immunological analyses as assessment of cytokines and immune cell profiling were conducted in the livers.ResultsWe showed that the receptors are essential for host survival, necessary to limit the fungal dissemination, and that their main effector functions can be related to shaping the T cell response, notably the cytotoxic CD8+ and Treg cell populations, instead of a conventional TH17 profile. While we also observed a contribution of IL-17 in the host defense, the cytokine is not involved in the restriction of the fungal growth.DiscussionOur results uncover dectin-1 and dectin-2 as novel determinants of protection against S. brasiliensis, but their effector function is not linked to the induction of IL-17 responses. Our fundings help to expand the understanding of the pathophysiology of this infection.